Penerapan Pendekatan Keterampilan Proses untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Sulastri, Arum (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The low learning outcomes of students in science subjects are caused by several factors, includingteachers only conveying science as a product and students memorizing factual information, thelearning experience in class is incomplete so that many students get scores below the KKM. Thisstudy aims to improve the learning outcomes of fourth grade students of SD Negeri 9 TumijajarTulang Bawang Barat in science subjects with the subject of energy and its changes using theProcess Skills Approach. This research is a collaborative classroom action research. The subjects in this study were fourth grade students of SD Negeri 9 Tumijajar Tulang Bawang Barat with a total of 20 students. This research took place in two cycles. Cycle 1 consists of 2 meetings and cycle 2 consists of 2 meetings. Data collection techniques in this study were observation,interviews, test techniques and documentation. The instruments used are student practicum sheets and multiple choice tests. Data analysis techniques used are quantitative techniques andqualitative techniques. The results showed that students' science learning outcomes had increased. This is indicated by the increase in the average value of the class at the time of pre-action 59.50 increased to 65.75 in the first cycle and then increased again in the second cycle to 76.00.